The Leadership and Political Dynamics of Japan’s Political Factions Within the Conservative Party: The Cases of the Normalization of Japan-Soviet Union Relations and Japan-People’s Republic of China Relations - Takahashi, Katsuyuki (Thai Journal of East Asian Studies, 2019)
This paper examines the leadership and political dynamics of Japan’s factions within the Liberal Democratic Party (LDP). By analyzing the decision-making process of the normalization of Japan-Soviet Union relations and Japan-People’s Republic of China relations, this article demonstrates that rather than being monolithic, the LDP is fissiparous comprising of several factions from the Right to the Center-left ideological camps. This makes the decisions on such controversial issues such as the normalization of relations with Socialist countries much more complicated. Under this circumstance, this paper contends that the role of political leaders has been essential in building coalition with several factions in the LDP and seeking support from other parties, interest groups and the public at large as well as negotiating with foreign governments.